2009
DOI: 10.1177/0149206309346734
|View full text |Cite
|
Sign up to set email alerts
|

Strategy in Network Industries: A Review and Research Agenda

Abstract: This article reviews extant theoretical perspectives and empirical literature at the nexus of network effects and strategy. Building on these insights, it offers a research framework that focuses on three primary avenues: the strategic drivers of network intensity, approaches to assess variations in network intensity, and effective strategies for leveraging network intensity. In doing so, the study widens the perspective of the role of strategy in network industries and offers directions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 59 publications
3
111
0
Order By: Relevance
“…Hence, existing literature seems to posit that the ultimate value proposition of the to-be-created innovation ecosystem can be constructed following an almost linear plan. The focus is thus put on questions of behavioral maneuvering -which is deduced from the clearly envisioned future -to ensure this value proposition will come true and that the focal firm becomes instrumental in this process (e.g., Adner & Kapoor, 2010;Ansari, Garud, & Kumaraswamy, 2015;Kapoor & Furr, 2015;McIntyre & Subramaniam, 2009;Wareham et al, 2014).…”
Section: New Value Propositions and Innovation Ecosystemsmentioning
confidence: 99%
“…Hence, existing literature seems to posit that the ultimate value proposition of the to-be-created innovation ecosystem can be constructed following an almost linear plan. The focus is thus put on questions of behavioral maneuvering -which is deduced from the clearly envisioned future -to ensure this value proposition will come true and that the focal firm becomes instrumental in this process (e.g., Adner & Kapoor, 2010;Ansari, Garud, & Kumaraswamy, 2015;Kapoor & Furr, 2015;McIntyre & Subramaniam, 2009;Wareham et al, 2014).…”
Section: New Value Propositions and Innovation Ecosystemsmentioning
confidence: 99%
“…Platform-based markets are often called winnertake-all markets, where only one platform may dominate and sustain its market leadership (see e.g., [3], [13]- [15]). This is due to the prevalence of positive indirect network effects ( [28]- [30]); the number of agents on one side of a platform tends to positively affect platform demand on the other market side(s), and vice versa ( [2], [27]).…”
Section: Multi-sided Platformsmentioning
confidence: 99%
“…This might not be a coincidence as platform-based markets are arguably characterized of winner-take-all dynamics. That is, the platform with the biggest installed base of buyers and sellers should sustain market leadership and basically take over the entire market, because of the prevalence of positive indirect network effects in platform-based markets ( [9], [10], [13]- [15]). Thus, multi-sided platforms are becoming the next major organizational form of interest to strategic management scholars seeking to explain sustained competitive advantage ( [1]- [4], [8]).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, McIntyre and Subramaniam (2009) list 22 empirical studies published over the last 25 years, while Birke (2009) reports a list of 37 research-based works identified over the past 28 years. Given the focus of this paper, we discuss a number of relevant studies in the past ten years.…”
Section: Literature Reviewmentioning
confidence: 99%